INCREASING COMPANY PERFORMANCE WITH LIQUIDITY, SOLVENCY IN CIGARETTE INDUSTRY LISTED IN IDX - Suprihati Suprihati; Abdul Haris Romdhoni; Gita Wahyu.A.M (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
In this study aims analyze the effect of financial ratios on the performance of cigarette companies listed on the IDX. The factors tested in this study are the effect of liquidity ratios, solvency ratios and activity ratios as independent variables while the company's profitability as the dependent variable. The sample in this study were all populations consisting of four companies and the data used are secondary data. The analytical tool used is multiple linear regression analysis at a significance level of 5%, with the regression equation Y = 0.180 + 0.006X1 - 0.014X2 + 0.090X3. In this study the influence of pritability is activity while liquidity and solvency do not affect profitability. And simultaneously obtained Fcount 5.381 is greater than Ftable 2.89 with a significance of 0.004 smaller than the significance value of α = 0.05, this shows that simultaneously Liquidity, Solvability and Activity are factors that influence profitability. Keywords : Profitability, Liquidity, Solvability, Activity